2019
DOI: 10.1002/adom.201900322
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nanosheets for Efficient All‐Optical Modulation and Logic Operation

Abstract: As the left neighbor of carbon in the periodic table, boron is very similar to carbon in electronic properties and strong bonding characters, and both undertake important roles in living organisms. [8][9][10][11] However, due to the unique trivalent electronic configuration, boron is among the most chemically versatile elements, which shows polymorphism in low-dimensional structures and thus richer properties, such as high-temperature superconductivity, high carrier mobility, massless Dirac fermions, superhard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The work with boron obtained a relatively fast rising time constant of 0.48 ms due to the superior photo-thermal response. 20 The work with graphene shows 0.51p phase shi at a low pump power of 5.3 mW due to the long interaction length of LDM graphene. 18 For MI structures with LDMs, three studies have been performed with antimonene, bismuthene and MXene respectively.…”
Section: Fiber All-optical Devices With a Pi Structurementioning
confidence: 94%
See 3 more Smart Citations
“…The work with boron obtained a relatively fast rising time constant of 0.48 ms due to the superior photo-thermal response. 20 The work with graphene shows 0.51p phase shi at a low pump power of 5.3 mW due to the long interaction length of LDM graphene. 18 For MI structures with LDMs, three studies have been performed with antimonene, bismuthene and MXene respectively.…”
Section: Fiber All-optical Devices With a Pi Structurementioning
confidence: 94%
“…The system structures of these ber alloptical devices can be generally classied into 2 main categories: non-resonant and resonant designs. For non-resonant designs, three typical designs will be discussed: they are Mach-Zehnder interferometer (MZI), 14,16,[18][19][20] Michelson interferometer (MI), 11,12,67 and polarization interferometer (PI). 13 For resonant design, micro-rings 95 will be discussed.…”
Section: Materials Characteristics and Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…All-optical phase shifters and switches play an important role for various all-optical applications including all-optical signal processing, sensing, and communication. It has been demonstrated that with 2D material-decorated microfiber photonic devices, the phase shifters and optical switches could be realized [277][278][279][280][281][282]. In 2015, Gan et al demonstrated an all-fiber phase shifter by employing graphene's optical absorption and excellent thermal properties [277].…”
Section: Phase Shifter and Optical Switchmentioning
confidence: 99%